An Integrated Approach to Improve the Performance of Green Architecture Industry Using Supply Chain Dimensions - Samireh Kadaei; Sama Jafari; Emaad Jeyzanibrahimzade; Masoud Ebrahimpour Taher; Mahsa Hashemi; Perisu Akar; Umit Akar (Complexity)
This study presents a holistic level of sustainability in the context of green architecture supply chains by integrating GSCM and GHRM through an integrated decision-making framework. The study applies a hybrid approach of neutrosophic fuzzy TOPSIS and fault tree analysis (FTA) with data mining to identify and rank critical barriers relating to sustainability, including insufficient government funding and technology challenges. This model offers practical recommendations for policymakers and practitioners aiming to improve green architecture considering GSCM and GHRM on supply chains. The analysis underscores the need for enhanced targeted policies and engagement from various stakeholders and the integration of digital technologies to strengthen sustainability efforts in the industry.